On and off the common ground: Japanese final particles as (un)grounding devices - Izutsu, Mitsuko Narita; Izutsu, Katsunobu (Lingua Posnaniensis, 2021)
The notion of “common ground” (Clark & Brennan 1991; Clark 1996) presupposes communication or conversation as “the basic setting for language use” (Clark 1996: 11). The serialisation of Japanese sentence-final particles is highly sensitive to the likelihood of the relevant utterance being part of the common ground. This paper reconsiders the conception of common ground and grounding processes, investigating monologic as well as conversational discourse. A case study of two modernist texts which contain internal monologue (interior monologue) illustrates how three facets of grounding activities (the establishment, confirmation, and cancellation of common ground) are tactfully realised by means of the final-particle marking of a distinction between monologic and conversational discourse. Our analysis reveals that Japanese final particles (specifically, -ne and -na(a)) play an essential role in encoding the speaker’s intention to ground or unground his/her utterance (i.e., to make the utterance on or off the common ground).